Bayesian analysis of biodiversity patterns via beam trawl versus video transect—a comparative case study of Svalbard rhodolith beds - Eileen Straube; Hermann Neumann; Max Wisshak; Gregor Mathes; Sebastian Teichert (Biodiversity and Conservation, 2024)
Knowledge of spatial biodiversity patterns is important for ecosystem assessment. Rhodoliths, free-living calcareous algae, are biotic components that structure the sea floor through their complex calcareous skeletons and their tendency to accumulate in an area to form rhodolith beds. Thereby, rhodoliths are considered to act as ecosystem engineers promoting local biodiversity. In this study, the biodiversity of rhodolith beds in Mosselbukta, Svalbard, was investigated to analyse the proposed link between local biodiversity and the presence of rhodoliths by evaluating beam trawl and underwater video transect data. The comparative analysis of two sampling methods addressing the same research question allowed us to assess the suitability of these two methods. To test our hypothesis and the utility of the two methods, evaluations of the two data sets were carried out separately by using Bayesian statistics. The results confirm a positive relationship between the presence of rhodoliths and local biodiversity with a posterior probability of 70% for the video transects and 85% for the beam trawl data. The similarity of the results of the two methods suggests that both methods are well-suited for the analysis of local biodiversity patterns. The combination of the two methods, with their individual strengths and weaknesses, has provided stronger support for the results and a broader view on different components of the biodiversity in the Svalbard rhodolith beds.

Growth hormone/IGF-I-dependent signaling restores decreased expression of the myokine SPARC in aged skeletal muscle - Sebastian Mathes; Alexandra Fahrner; Edlira Luca; Jan Krützfeldt (Journal of Molecular Medicine, 2022)
Skeletal muscle exerts many beneficial effects on the human body including the contraction-dependent secretion of peptides termed myokines. We have recently connected the myokine secreted protein acidic and rich in cysteine (SPARC) to the formation of intramuscular adipose tissue (IMAT) in skeletal muscle from aged mice and humans. Here, we searched for inducers of SPARC in order to uncover novel treatment approaches for IMAT. Endurance exercise in mice as well as forskolin treatment in vitro only modestly activated SPARC levels. However, through pharmacological treatments in vitro, we identified IGF-I as a potent inducer of SPARC expression in muscle cells, likely through a direct activation of its promoter via phosphatidylinositol 4,5-bisphospate 3-kinase (PI3K)-dependent signaling. We employed two different mouse models of growth hormone (GH)/IGF-I deficiency to solidify our understanding of the relationship between IGF-I and SPARC in vivo. GH administration robustly increased intramuscular SPARC levels (3.5-fold) in GH releasing hormone receptor-deficient mice and restored low intramuscular SPARC expression in skeletal muscle from aged mice. Intramuscular glycerol injections induced higher levels of adipocyte markers (adiponectin, perilipin) in aged compared to young mice, which was not prevented by GH treatment. Our study provides a roadmap for the study of myokine regulation during aging and demonstrates that the GH/IGF-I axis is critical for SPARC expression in skeletal muscle. Although GH treatment did not prevent IMAT formation in the glycerol model, targeting SPARC by exercise or by activation of IGF-I signaling might offer a novel therapeutic strategy against IMAT formation during aging. Key messages IGF-I regulates the myokine SPARC in muscle cells directly at the promoter level. GH/IGF-I is able to restore the decreased SPARC levels in aged skeletal muscle. The glycerol model induces higher adipocyte markers in aged compared to young muscle. GH treatment does not prevent IMAT formation in the glycerol model.

Reply to: Could superimposed electromyostimulation be an effective training to improve aerobic and anaerobic capacity? Methodological considerations for its development - Sebastian Mathes; Patrick Wahl (European Journal of Applied Physiology, 2017)

Chronic effects of superimposed electromyostimulation during cycling on aerobic and anaerobic capacity - Sebastian Mathes; Niklas Lehnen; Tobias Link; Wilhelm Bloch; Joachim Mester; Patrick Wahl (European Journal of Applied Physiology, 2017)